Intensification of the Biohydrogen Production Process - Nataliia Golub; Liudmyla Zubchenko; Iryna Demianenko; Yumei Zhang; Nataliia Seminska (Innovative Biosystems and Bioengineering, 2024)
Background. In the last decades, humanity has faced the challenge of finding new ways to obtain renewable, environmentally friendly energy carriers. Hydrogen is one of such energy carriers; however, the current methods of its production require fossil fuels and are accompanied by significant CO2 emissions. Consequently, the energy costs needed to obtain hydrogen by electrolysis exceed the amount of energy produced by burning the hydrogen. Simultaneously, the hydrogen yields for alternative ways, such as fermentation, remain low.